STUDY OF MANAGEMENT OF KEARSIPAN EFFICIENCY OF EMPLOYEES PERFORMANCE IN OFFICE UPT LIBRARY IN KUTAI TIMUR REGENCY. - Firmansyah, Reksi (PREDIKSI, 2016)
ABSTRACTÂ Reksi Firmansyah. STUDY OF MANAGEMENT OF KEARSIPAN EFFICIENCY OF EMPLOYEES PERFORMANCE IN OFFICE UPT LIBRARY IN KUTAI TIMUR REGENCY. Each organization, whether large or small, must have a goal to be achieved, to achieve that goal every organization must have a place as an office. Each office must require a unit that manages everything related to administrative activities. Administration activity is a wide scope of activities, usually all administrative activities are processed in a separate unit called the administration, administration, secretariat, office and so forth. Administrative activities in an office basically also have a result like other units. The results or products of an office are letters, forms, and reports. The management of letters, forms, and reports produced and received by an office will ultimately relate to archives. So, the administrative activity is basically produce, receive, process, and store various letters, forms, reports and so forth. Office of the Library Unit of East Kutai Regency is one of the government offices that serve the public interest that will not be separated from archival activities. Office that daily handles library membership card, storage of documents or other documents, makes the office has various archives. Success in archive management is determined by many things. Filing factors such as storage systems, archiving employees, archival equipment, and of course with work environment. The management of archives conducted at the Office of the District Library of East Kutai Regency greatly affects the success or failure of the reinvention of the archives. Observations made at The Office of UPT Library of East Kutai Regency shows that in carrying out the archive management of the office still not fully implement the archive management because it is caused by several factors. These factors include the limited costs for the procurement of archive management facilities.Â Keyword: | Archive Management, Efficiency, UPT Kutai Timur Library